BIOPROSPEK AKTIVITAS METABOLIT SEKUNDER DARI LAMUN (Seagrass) DAN BEBERAPA JENIS MAKROALGA (Seaweeds) SEBAGAI KANDIDAT AGEN ANTIBAKTERI PATOGEN Vibrio harveyi YANG MENYERANG UDANG WINDU (Penaeus monodon) (Studi in-vitro) - Kurnia Agung, Mochamad Untung; Mulyani, Yuniar; Riyantini, Indah (Jurnal Harpodon Borneo, 2012)
Bacterial deseases are seriousness problem in aquaculture. The uncontrolled of quality degradation of pond sites because of wastes and organic matters decompotition and also global climate changes has been predicted affect triggered the bacterial infections. Vibrio harveyi is one of patogenic bacteria which againts Tiger shrimp (Penaeus monodon). The recovery strategies has been applied both in the rehabilitation of pond sanitary and also it has been focussed in curative methods to overcome infection activities. The usage of synthetic antibiotics has been reported gift any negative effects, either for environment and rised pathogenic resintance because of uncontrolled exposure.Environmental friendly and based on biological methods has been promoted to overcome this problem. The usage of antibacterial agents derived from natural compounds has been recommended as an effective method. Several marine resources has been predicted as candidates of antibacterial agents againts Vibrio harveyi. Several seaweeds (macroalga) and seagrass has been explored in this research at in-vitro level of study to inhibit the activity of Vibrio harveyi. The result showed that all of the crude extracts derived from seagrass (Thallasia sp) and several kinds of seaweeds (Padina sp, Gracilaria sp and Sargassum sp) could inhibit the growth of Vibrio harveyi from the lowest concentration level (10 µg/mL). The highest inhibition activity has been showed from the antibacterial sensitivity test of crude extract of Thallasia sp at the concentration level of 10.000 µg/mL. Keywords : macroalgae, seagrass, secondary metabolite, antibacteria, Vibrio harveyi